Using SISPEL Application for Character Building of Students in Vocational High School - Munawar Munawar; Lailatul Musyarofah; Eka Fadilah; Lestariningsih Lestariningsih (Acitya: Journal of Teaching and Education, 2024)
This study delves into the effects of the SISPEL (Sistem Pelanggaran) application on character development among students in vocational high schools. Specifically, it focuses on 23 students from the Vocational High School Khusus Angkatan Laut - 1 Surabaya, who have been identified for violating school rules. By exclusively employing the SISPEL application, the research intricately examines its role in shaping character traits within the context of vocational education. Through a meticulous questionnaire-based survey, the study endeavors to highlight the application's influence on ethical values, moral principles, and the cultivation of character-building skills. The primary goal is to unveil the multi-dimensional impact it has on fostering holistic student development. The findings of this exploration not only enrich the current comprehension of character development within this specific educational framework but also offer insights into the potential of technology-driven tools like SISPEL to cultivate well-rounded individuals. This research contributes to the broader discourse on character education and underscores the significance of innovative approaches in molding the ethical and moral foundation of students.